Artificial intelligence training in media: addressing technical and ethical challenges for journalists and media professionals - Sarrionandia, Barbara; Peña-Fernández, Simón; Ángel Pérez-Dasilva, Jesús; Larrondo-Ureta, Ainara (Frontiers in Communication, 2025)
The rise of Artificial Intelligence (AI) is presenting both technical and ethical challenges for media organisations, creating an urgent need for professional training. This study explores how media professionals in the Basque Country are equipping themselves to face these challenges. Using a mixed-method approach, it combines a survey of 504 active professionals with in-depth interviews with six innovation leaders from major regional media outlets. The findings reveal that only 14.1% of professionals have undergone AI training, mostly through self-learning. Larger, internationally focused companies are more proactive in providing training, while local and traditional media organisations show significant gaps. Technical and managerial roles are leading the way in adopting AI, whereas newsroom staff are notably behind. The study highlights the pressing need to enhance AI training, with a particular focus on ethical and technical aspects, both through in-house programmes and formal education pathways.